Isolation and characterization of the alpha-sialyl-beta-2,3-galactosyl-specific adhesin from fimbriated Escherichia coli. - Moch, T (1987)
The alpha-sialyl-beta-2,3-galactosyl-specific adhesin (S adhesin) was isolated from cells of a recombinant Escherichia coli K-12 strain expressing the S-fimbrial adhesin complex. A crude cell extract was partially dissociated into fimbriae and an adhesin-enriched fraction by heating to 70 degrees C. From the latter, adhesin was purified to apparent homogeneity (by fast protein liquid chromatography, immunoblot, and NaDodSO4/PAGE) by differential ammonium sulfate precipitation, dissociation in 8 M guanidine hydrochloride, and high-resolution anion-exchange chromatography in 8 M urea. The purified adhesin formed an aggregate of Mr approximately 10(6) that was made up of one type of 12-kDa polypeptide (fimbrillin is 16.5 kDa). It had pI value of 4.7 (fimbriae has a pI value of 6). Adhesin and fimbrillin had different amino acid compositions. The purified adhesins agglutinated human and bovine erythrocytes with the same specificity as the whole bacteria; purified fimbriae were not adhesive. Monoclonal anti-adhesin and anti-fimbriae antibodies were obtained. Monoclonal anti-adhesin, but none of the anti-fimbriae, antibodies inhibited the agglutination of erythrocytes. The anti-adhesive antibodies were used in immuno-gold electron microscopy to localize adhesin exclusively on the fimbriae, with a possible preference to their tips.